Establishment and directed differentiation of induced pluripotent stem cells from glycogen storage disease type Ib patient. (28th October 2013) - Satoh, Daisuke; Maeda, Tohru; Ito, Tetsuya; Nakajima, Yoko; Ohte, Mariko; Ukai, Akane; Nakamura, Katsunori; Enosawa, Shin; Toyota, Masashi; Miyagawa, Yoshitaka; Okita, Hajime; Kiyokawa, Nobutaka; et al.
<x xml:space="preserve">Abstract</x> Glycogen storage disease type Ib (GSDIb) is caused by a deficiency in the glucose‐6‐phosphate transporter (G6PT), which leads to neutrophil dysfunction. However, the underlying causes of these dysfunctions and their relationship with glucose homeostasis are unclear. Induced pluripotent stem cells (iPSCs) hold a great promise for advances in developmental biology, cell‐based therapy and modeling of human disease. Here, we examined the use of iPSCs as a model for GSDIb. In this study, one 2‐year‐old patient was genetically screened and diagnosed with GSDIb. We established iPSCs and differentiated these cells into hepatocytes and neutrophils, which comprise the main pathological components of GSDIb. Cells that differentiated into hepatocytes exhibited characteristic albumin secretion and indocyanine green uptake. Moreover, iPSC‐derived cells generated from patients with GSDIb metabolic abnormalities recapitulated key pathological features of the diseases affecting the patients from whom they were derived, such as glycogen, lactate, pyruvate and lipid accumulation. Cells that were differentiated into neutrophils also showed the GSDIb pathology. In addition to the expression of neutrophil markers, we showed increased superoxide anion production, increased annexin V binding and activation of caspase‐3 and caspase‐9, consistent with the GSDIb patient's neutrophils. These results indicate valuable tools for the analysis of this pathology and the development of future treatments.